Common wealth : contemporary poets on Pennsylvania - Maddox, Marjorie, 1959-; Wemple, Jerry (Book collections on Project MUSE., 2005)
Over the years, Pennsylvania has been graced with an abundance of writers whose work draws imaginatively on the state's history and culture. Common Wealth sings the essence of Pennsylvania through contemporary poetry. Whether Pennsylvania is their point of origin or their destination, the featured poets ultimately find what matters: heritage, pride, work, inventiveness, struggle, faith, beauty, hope. Keystone poets Marjorie Maddox and Jerry Wemple celebrate Pennsylvania with this wide range of new and veteran poets, including former state poet Samuel Hazo, National Book Award winner Gerald Stern, Pulitzer Prize winners Maxine Kumin, W. S. Merwin, and W. D. Snodgrass, and Reading-born master John Updike. The book's 103 poets also include such noted authors as Diane Ackerman, Maggie Anderson, Jan Beatty, Robin Becker, Jim Daniels, Toi Derricotte, Gary Fincke, Harry Humes, Julia Kasdorf, Ed Ochester, Jay Parini, Len Roberts, Sonia Sanchez, Betsy Sholl, and Judith Vollmer. In these pages, poems sketch the landscapes and cultural terrain of the state, delving into the history, traditions, and people of Philadelphia, "Dutch" country, the coal-mining region, the Poconos, and the Lehigh Valley; the Three Rivers region; the Laurel Highlands; and Erie and the Allegheny National Forest. Theirs is a complex narrative cultivated for centuries in coal mines, kitchens, elevated trains, and hometowns, a tale that illuminates the sanctity of the commonplace--the daily chores of a Mennonite housewife, a polka dance in Coaldale, the late shift at a steel factory, the macadam of the Pennsylvania Turnpike. With its panoramic vision of Pennsylvania, its culture, and its thriving literary heritage, Common Wealth is a collection of remembrance for a state that continues to inspire countless contributions to American literature.